Analisis Proses Kolaborasi Dalam Pembinaan Anakjalanan Di Panti Sosial Asuhan Anak Putrautama 2 Tahun 2022 - EUIS KOMARIAH; Tri Ubayanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this research is to identify the analysis of collaboration process in training street children at Anak Putra Utama 2 Orphanage in 2022. This research uses qualitative descriptive method to describe and explain in detail the existing phenomena by using interview as its supporting instrument. The result of this research shows that the collaboration process in training street children at Anak Putra Utama 2 Orphanage in 2022 is not well established. The obstacles include the lack of competent human resources. The efforts which can be made include developing the human resource competency and adding personnel.